Bilateral repetitive transcranial magnetic stimulation ameliorated sleep disorder and hypothalamic–pituitary–adrenal axis dysfunction in subjects with major depression - Chen, Xing; Jiang, Fei; Yang, Qun; Zhang, Peiyun; Zhu, Haijiao; Liu, Chao; Zhang, Tongtong; Li, Weijun; Xu, Jian; Shen, Hongmei (Frontiers in Psychiatry, 2022)
Objective: In this study, we sought to explore the effectiveness of bilateral repetitive transcranial magnetic stimulation (rTMS) over dorsolateral prefrontal cortex (DLPFC) on depressive symptoms and dysfunction of hypothalamic-pituitary-adrenal (HPA) axis in patients with major depressive disorder (MDD). Methods: One hundred and thirty-eight adults with MDD were administrated drugs combined with three weeks of active rTMS (n = 68) or sham (n = 68) treatment. The 17-item Hamilton Depression Rating Scale for Depression (HAMD-17) was to elevate depression severity at baseline and weeks 4. To test the influence of rTMS on HPA axis, plasma adrenocorticotropic hormone (ACTH) and serum cortisol (COR) were detected at pre- and post-treatment. Results: No statistical significance was found for baseline of sociodemographic, characteristics of depression, and psychopharmaceutic dosages between sham and rTMS groups (p > 0.05). There was a significant difference for HAMD-17 total score between the two groups at end of four weeks after treatment (p < 0.05). Compared to the sham, rTMS group demonstrated a more significant score reduction of HAMD-17 and sleep disorder factor (HAMD-SLD) including sleep onset latency, middle awakening and early awakening items at end of four-week after treatment (p < 0.05). Furthermore, total score reduction of HAMD-17 was correlated with decrease in plasma ACTH, not in COR, by rTMS stimulation (p < 0.05), and the effect of rTMS on HAMD-17 total score and plasma ACTH occurred specifically in male MDD patients. Conclusion: Bilateral rTMS for three weeks ameliorated depression via the improvement of sleep disorder, and plasma ACTH is a predictor for the efficacy of rTMS, especially in male MDD patients.